Use of short-tandem repeat (STR) fingerprinting to validate sample origins in hepatitis C virus molecular epidemiology studies - Edwards, Victoria C.; McClure, Patrick; Brown, Richard J.P.; Thompson, Emma; Irving, William L.; Ball, Jonathan K. (Society for General Microbiology, 2014)
Sequence analysis is used to define the molecular epidemiology and evolution of the hepatitis C virus. Whilst most studies have shown that individual patients harbour viruses that are derived from a limited number of highly related strains, some recent reports have shown that some patients can be co-infected with very distinct variants whose frequency can fluctuate greatly. Whilst co-infection with highly divergent strains is possible, an alternative explanation is that such data represent contamination or sample mix-up. In this study, we have shown that DNA fingerprinting techniques can accurately assess sample provenance and differentiate between samples that are truly exhibiting mixed infection from those that harbour distinct virus populations due to sample mix-up. We have argued that this approach should be adopted routinely in virus sequence analyses to validate sample provenance.